Bibliometric analysis of potassium channel research. Issue 1 (1st January 2020) - Shi, Jingjing; Shi, Shuqing; Shi, Shuai; Jia, Qiulei; Yuan, Guozhen; Chu, Yuguang; Wang, Huan; Hu, Yuanhui; Cui, Hanming
ABSTRACT: ABSTRACT Objective: To explore the research status, hotspots, and trends in research on potassium channel. Methods: The Web of Science core collection database was used as the data source and the visual analysis software Citespace5.4 R3 was used to visualize the studies of potassium channel in the past 10 years. The national/institutional distribution, journal distribution, authors, and related research were discussed. Results 17, 392 articles were obtained. The USA, Peoples R China, Germany, England, and Japan were the main countries in the field and University of California was the most important institution for the study of potassium channel. PLoS One was the most productive journal and proceedings of the national academy of sciences of the united states of america was the most frequently cited journal in potassium channel research. The author with the highest number was Colin G Nichols and the author with the highest co- cited frequency was Sanguinetti MC. The three hot spots of potassium channel research were gene expression, Ca2+ activated k+ channel and nitric oxide. The top four research frontiers of potassium channel research were bk channel, blood pressure, oxidative stress and electrophysiology. Conclusion The study provides a perspective for understanding the potassium channel research and provides valuable information for potassium channel researchers to identify potential collaborators, partner institutions, hot topics and research frontiers.